Attitudinal perception of cosmetic wear and damage of materials within the use phase of portable electronic products - Alan H.G. Manley (2018)
During the use phase of products, a series of obsolescing factors contribute to why a product is disposed of. Currently the visual state of a product is considered primarily in terms of aesthetic obsolescence which is synonymous with influential factors such as changes in fashion or personal preferences in style. The physical condition of a product is not commonly understood within the context of product replacement and the physical changes due to use are not understood fully. The research contributes to and provides original empirical research findings for the current literature on product lifetime extension, material semantics, the circular economy, emotionally durable design and material culture. Through an initial exploratory study (Photographic Analysis (PA) Study) of previously unexplained types of wear and damage that occur on portable electronic devices a taxonomy of damage (TOD) was established which provided the nomenclature for further studies. The second study (Retrospective Assessment (RA) Study) established the attitudes to wear based on the wear type, location, material and the stage during ownership that the wear occurred at. The RA Study highlighted the differences in the attitudinal responses to differing types of wear and damage and identified the differences in the temporal assessments of wear and damage. A third study (Real Time Assessment (RTA) Study) aimed to confirm or repudiate the findings found in the RA Study. The focus during the study was attitudes to the wear and damage in relation to the differences in materials, the location of the wear and the type of wear and damage was also looked at and led to a fuller understanding of how products and materials are perceived during the use phase; a stage of the product lifetime that is not currently well understood in terms of users aesthetic or cosmetic sensibilities. The final study (Semantic Perception of Materials (SPM) Study) focused on the visual and tactile perceptions of materials. The study established attitudinal perceptions of wear and damage of materials with a quantitative research methodology which has produced a better understanding of material semantics within the context of electronic objects. Through the four studies, discussion topics arose and major findings of the doctoral study were drawn out and seen to be interesting enough for further research and study. These discussions include the importance of including cosmetic obsolescence into the lexicon of product obsolescence and product lifetime extension literature, the differences in the perceptions of materials when they are within the context of a product or being assessed as samples, how differing product contexts affect user perceptions of wear and damage on materials and the potential inclusion of a material wear index that could inform the material selection process that goes further than the technical aspects outlined in current material selection tools and literature.